CARA MENGURANGI BAKTERI JAHAT DI RONGGA MULUT DENGAN METODE "SIBENUR" PADA KOMUNITAS SMP ISLAM AL AZHAR 08 BEKASI. - Ciptadhi Tri Oka Binartha; Meiny Faudah Amin; Sri Ratna Laksmiastuti; Yessy Ariesanti (JURNAL ABDIMAS KESEHATAN TERPADU, 2022)
According to Riskesdas data in 2018, the prevalence of caries in Indonesia is 66% and data on toothbrush behavior in the population aged 3 years and over shows that the correct brushing behavior is still below 4%. The covid-19 pandemic situation that is still unfinished has delayed the maintenance of dental and oral health, especially routine examinations of dental and oral health The school age period is the most important time to start maintaining healthy teeth and mouth, this is because the good quality of health is a reflection of the quality of human resources. In an effort to help deal with this problem, counseling and education were carried out on how to maintain oral and dental health in the Al Azhar 8 Islamic junior high school (SMPI) community, Bekasi. The purpose of this activity is to increase knowledge and provide training on how to maintain and care for dental and oral health while at home. The method used in this counseling and training is carried out online using the zoom application. The main material given to the participants was to introduce how to maintain oral and dental health with the "SIBENUR" method (dental floss brush and gargle). This method can make it easier for counseling participants to remind them how to maintain healthy teeth and mouth at home. Evaluation of knowledge improvement in this counseling uses pretest and post test using the Google Form. The aims of this test is to measure the level of knowledge. The results obtained from 3 groups of respondents divided by class group showed data on an average increase in knowledge of 76%. It is hoped that this increase in knowledge can also improve the degree of dental and oral health in the community, especially in the target partner community